Aplikasi Media Pembelajaran Pendidikan Pancasila Kelas 1 SD Berbasis Android - Fikri Sahira Al-Mahdi; Sigit Sugiyanto; Tito Pinandita; Feri Wibowo (Jurnal Teknologi Informasi dan Multimedia, 2026)
The learning process of Pancasila Education in elementary schools requires learning media that can improve students’ engagement and learning interest. This study aims to develop an An-droid-based learning media application for first-grade elementary school Pancasila Education as an interactive learning medium. The development method used in this study is Multimedia Devel-opment Life Cycle (MDLC), which consists of concept, design, material collecting, assembly, test-ing, and distribution stages. The developed application provides learning materials, interactive drag-and-drop quizzes, and multiple-choice tests. System testing was conducted using the black box method to ensure that all application features function properly. In addition, usability testing involved 18 students using the System Usability Scale (SUS) instrument and obtained an average score of 79,17, which is included in the "Acceptable" category with a "Good" adjective rating. The results indicate that the application is easy to use, attractive, and helpful in supporting students’ learning process. Therefore, the developed application can be used as an interactive learning me-dium for Pancasila Education in elementary schools.